2010
DOI: 10.1039/c0cc00363h
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of superior dispersion of chemically converted graphene in organic solvents

Abstract: Chemically converted graphene that was reduced with phenylhydrazine was highly dispersed in organic solvents, and its "paper" prepared by filtration of the reduced graphene possessed an electrical conductivity value as high as 20,950 S m(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(77 citation statements)
references
References 23 publications
4
73
0
Order By: Relevance
“…[37][38][39] For example, the CCG prepared by the reduction of graphene oxide with phenylhydrazine is dispersible in various polar aprotic organic solvents such as N,N′-dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), propylene carbonate (PC), and 1-methyl-2-pyrrolidinone (NMP). The organic dispersions are stable at room temperature for at least 2 months.…”
Section: Structurementioning
confidence: 99%
“…[37][38][39] For example, the CCG prepared by the reduction of graphene oxide with phenylhydrazine is dispersible in various polar aprotic organic solvents such as N,N′-dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), propylene carbonate (PC), and 1-methyl-2-pyrrolidinone (NMP). The organic dispersions are stable at room temperature for at least 2 months.…”
Section: Structurementioning
confidence: 99%
“…16,[56][57][58] The primary method of exfoliation of GO is ultrasonication in aqueous, 50 binary 59 or organic solvents; 51 however, spontaneous exfoliation of extra-large sheets of GO to form stable dispersions in different solvents has also been achieved. 2,3,52,56,58,60 Ogino et al 54 reported the exfoliation of graphite oxide in water without sonication. The authors used a new approach of rapid freezing of an aqueous solution containing graphite oxide and subsequent thawing of the resultant solid.…”
Section: Exfoliation Of Graphite Oxidementioning
confidence: 99%
“…Therefore, expanded graphite was found to be the best precursor for making GO containing large sheets. 52,60 The most common choice of intercalation compound is graphite bisulphate, which can be expanded along the c-axis via rapid thermal heating at 1050°C for 15 s. 3,16,56 This rapid heating, results in thermal decomposition of the intercalants into gaseous species that overcomes the van der Waals attractions and forces the carbon layers apart. During thermal expansion, the graphite expands up to~300 times along the c axis to transform the graphite platelets into worm shaped expanded graphite ( Figure 4).…”
Section: Thermal Expansion Of Intercalated Graphitementioning
confidence: 99%
“…Addition of H 2 occurs across the alkenes, coupled with the extrusion of nitrogen gas, large excess of NaBH 4 have been used as a reducing agent [102]. Other reducing agents used include phenyl hydrazine [103], hydroxylamine [104], glucose, [105] ascorbic acid [106], hydroquinone [107], alkaline solutions [108], and pyrrole [109]. GO was formed by the chemical reaction between organic isocyanates and the hydroxyl is shown in Fig.…”
Section: Reduction Graphene Oxidementioning
confidence: 99%